2015
DOI: 10.3109/10408363.2015.1084990
|View full text |Cite
|
Sign up to set email alerts
|

Sugar consumption, metabolic disease and obesity: The state of the controversy

Abstract: The impact of sugar consumption on health continues to be a controversial topic. The objective of this review is to discuss the evidence and lack of evidence that allows the controversy to continue, and why resolution of the controversy is important. There are plausible mechanisms and research evidence that support the suggestion that consumption of excess sugar promotes the development of cardiovascular disease (CVD) and type 2 diabetes (T2DM) both directly and indirectly. The direct pathway involves the unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
425
1
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 580 publications
(446 citation statements)
references
References 156 publications
(213 reference statements)
4
425
1
16
Order By: Relevance
“…(9) It is important to bear in mind that SSB intake can promote cardio- Long-term, high SSB intake can elicit direct and indirect effects in the body. The glucose and fructose components making up SSBs can trigger perturbations that lead to downstream metabolic and functional effects.…”
Section: Scientific Advisory Committee On Nutrition and Americanmentioning
confidence: 99%
“…(9) It is important to bear in mind that SSB intake can promote cardio- Long-term, high SSB intake can elicit direct and indirect effects in the body. The glucose and fructose components making up SSBs can trigger perturbations that lead to downstream metabolic and functional effects.…”
Section: Scientific Advisory Committee On Nutrition and Americanmentioning
confidence: 99%
“…Concomitant with the increased incidence and prevalence of obesity and metabolic syndrome, the consumption of fructose has increased around 30% in the last 40 years [4]. More specifically, because fructose is less able to promote satiety and is more palatable, it will stimulate a higher consumption of food [4], and alter the metabolism of lipids and carbohydrates, thereby favouring the synthesis and accumulation of fat [5]. The accumulation of adipose tissue has come to be considered a global public health problem.…”
Section: New Story/old Enemymentioning
confidence: 99%
“…sucrose) produce greater degrees of metabolic abnormalities than does glucose (either isolated as a monomer, or in chains as starch) and may present greater risk of CHD. To reduce the burden of CHD, guidelines should focus particularly on reducing intake of concentrated sugars, specifically the fructose-containing sugars like sucrose and high-fructose corn syrup in the form of ultra-processed foods and beverages [19] Others have found that consumption of added sugar is associated with development and/or prevalence of fatty liver, dyslipidemia, insulin resistance, hyperuricemia, CVD and type 2 diabetes and failure to stimulate leptin production [20][21][22][23].…”
Section: High Sugar Intake Increases Risk For Cardiovascular Diseasementioning
confidence: 99%